Advances in Compiler Construction for Adaptive Computers - Benjamin, Ubokobong Effiong (Research Parks Publishers, 2022)
This paper is focused on advances in compiler construction for adaptive computers. Compiler construction is the process of constructing compilers and a compiler converts a source code into a machine code for implementation. A classical compiler is targeted to a specific hardware and processor configuration while an adaptive compiler adapts to different hardware and processor configurations making it very efficient. The term compilation denotes the conversion expressed in a human oriented source language to an equivalent algorithm expressed in a hardware oriented target language. Adaptive systems, on the other hand, accelerate programs by executing parts of the algorithm on adaptive hardware. These elements can be dynamically reconfigured during the program run. This has given rise to adaptive computers. Adaptive compiler is therefore responsible for possibility of adaptive computer systems. This makes research on adaptive compiler construction for adaptive computers important. The aim of this paper is therefore to reveal how adaptive compiler construction has influenced the development of adaptive computers.